Clinical relevance of Scedosporium spp. and Exophiala dermatitidis in patients with cystic fibrosis: A nationwide study. (6th February 2020) - de Jong, C C M; Slabbers, L; Engel, T G P; Yntema, J B; van Westreenen, M; Croughs, P D; Roeleveld, N; Brimicombe, R; Verweij, P E; Meis, J F; Merkus, P J
Abstract: An increased prevalence of various filamentous fungi in sputum samples of patients with cystic fibrosis (CF) has been reported. The clinical significance, however, is mostly unclear. The aim of this study was to investigate the clinical relevance of Scedosporium spp. and Exophiala dermatitidis from sputum samples of patients with CF in the Netherlands. In this cross-sectional study, all CF patients of the Dutch national CF registry who were treated at five of the seven recognized CF centers during a 3-year period were included. We linked clinical data of the national CF registry with the national Dutch filamentous fungal database. We investigated the association between clinical characteristics and a positive sputum sample for Scedosporium spp. and E. dermatitidis, using logistic regression. Positive cultures for fungi were obtained from 3787 sputum samples from 699 of the 1312 patients with CF. Scedosporium spp. was associated with severe genotype, CF-related diabetes, several microorganisms, and inhaled antibiotics. E. dermatitidis was associated with older age, female sex, and Aspergillus spp. CF patients with and without Scedosporium spp. or E. dermatitidis seemed comparable in body mass index and lung function. This study suggests that Scedosporium spp. and E. dermatitidis are probably no major pathogens in CF patients in the Netherlands. Greater understanding of epidemiologic trends, risk factors, and pathogenicity of filamentous fungi in the respiratory tracts of patients with CF is needed.